Executive Committee Minutes 2016-01-28 - Academic Senate:::::::::
Agenda – Approved. Minutes of 12/10/15 – Approved. Chair Report. Revision to the POLS Major approved for the consent calendar for the Senate. Revision to the Reappointment, Tenure and Promotion policy approved as a business item for the Senate. Revision to Arts BA/BFA Photography concentration approved for the consent calendar for the Senate. President Report. Report from the Ad Hoc classroom upgrade group. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. EPC Report. FSAC Report. SAC Report. CFA Report. First pass on electronic agenda. Senate agenda approved.